THE IMPACT OF GILTI AND FDII ON THE INVESTMENT LOCATION CHOICE OF U.S. MULTINATIONALS - Singh, Kartikeya; Mathur, Aparna (Columbia Journal of Tax Law, 2019)
This article analyzes the impact of two new international tax provisions, GILTI and FDII, passed under the Tax Cuts and Jobs Act, on U.S. multinational corporations’ location of new capital. We analyze whether these rules help retain internationally mobile rents within the U.S. tax base and the associated economic activity within the United States. Our analysis suggests that for a wide range of investment profiles (characterized in terms of scale and expected above-normal returns) for intangible capital, a U.S. MNC can do better by locating a new investment in the United States.